2021
DOI: 10.1016/j.mayocpiqo.2021.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cost Conversation on Decision-Making Outcomes

Abstract: Objective: To understand the impact of cost conversations on the following decision-making outcomes: patients' knowledge about their conditions and treatment options, decisional conflict, and patient involvement.Patients and Methods: In 2020 we performed a secondary analysis of a randomly selected set of 220 video recordings of clinical encounters from trials run between 2007 and 2015. Videos were obtained from eight practice-based randomized trials and one preepost-prospective study comparing care with and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…We had previously conducted 3 studies showing that cost conversations have a minimal but favorable effect on decision-making but not on cost-reducing outcomes in clinical encounters, particularly when they occur in encounters aided by a shared decision-making tool. 5 Further cost conversations were associated with patients’ consideration of treatment cost burden but not the final treatment choice. 6 We also found that using shared decision-making tools that raise cost as an issue increased the occurrence of cost conversations but were less likely to address cost issues or offer potential solutions to patients’ cost concerns.…”
Section: Resultsmentioning
confidence: 99%
“…We had previously conducted 3 studies showing that cost conversations have a minimal but favorable effect on decision-making but not on cost-reducing outcomes in clinical encounters, particularly when they occur in encounters aided by a shared decision-making tool. 5 Further cost conversations were associated with patients’ consideration of treatment cost burden but not the final treatment choice. 6 We also found that using shared decision-making tools that raise cost as an issue increased the occurrence of cost conversations but were less likely to address cost issues or offer potential solutions to patients’ cost concerns.…”
Section: Resultsmentioning
confidence: 99%
“…3 A discussion on the potential benefi ts, risks, and cost, as suggested in the article, would be valuable in guiding clinical decisions. 4 Furthermore, the authors provide an excellent overview of diet as secondary prevention, particularly emphasizing the superiority of a Mediterranean diet over a low-fat diet. However, it might be pertinent to explore the feasibility and accessibility of such dietary recommendations for patients, considering cultural and socioeconomic factors.…”
mentioning
confidence: 99%